Strategi Pengembangan Usaha Ternak Sapi Potong di Masa Pandemi pada UD. Terobos Kabupaten Kupang - Dani Agung Wicaksono; M. Habbib Khirzin; Annisa Syachril (Yayasan Literasi Sains Indonesia, 2023)
This research aims to know internal and external factors and determine the right strategies for the development of beef cattle business in UD. Terobos. The method used is qualitative and quantitative with the determination of respondents in purposive sampling. This data is processed using SWOT analysis as a formulation of strategy and QSPM as a decision strategy. The results of this study indicate that UD. Terobos has 4 strengths, 2 weaknesses, 4 opportunities, and 3 threats. The IFAS evaluation value in this study was 2.813 and the EFAS evaluation value was 2.851. The results of the IE matrix show UD. The breakthrough is in the V quadrant position, this condition is classified into grow and stability. This shows that the company needs a strategy to grow better. The results of the SWOT analysis show 4 alternative strategies that can be recommended for the development of UD. Break through. The results of the QSPM priority marketing strategy suggested are holding regular livestock program training by the government to increase the scale of beef cattle business to become more advanced (S-O) with a TAS (Total Attractive Score) value of 5.393.